2017
DOI: 10.1257/pol.20140383
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Response to State Energy Efficient Appliance Rebate Programs

Abstract: Through an evaluation of the 2009 Recovery Act's State Energy Efficient Appliance Rebate Program, this paper examines consumers' response to energy efficiency rebates. The analysis shows that 70 percent of consumers claiming a rebate were inframarginal and an additional 15 percent–20 percent of consumers simply delayed their purchases by a few weeks. Consumers responded to rebates by upgrading to higher quality, but less energy-efficient models. Overall the impact of the program on long-term energy demand is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The average rebate amount was $128, and the state rebates varied from $50 to $600. Some programs lasted for only one day (e.g., Illinois and Texas); the longest‐running program was in Alaska, and lasted 639 days (Houde and Aldy, ).…”
Section: Data and Environmentmentioning
confidence: 99%
“…The average rebate amount was $128, and the state rebates varied from $50 to $600. Some programs lasted for only one day (e.g., Illinois and Texas); the longest‐running program was in Alaska, and lasted 639 days (Houde and Aldy, ).…”
Section: Data and Environmentmentioning
confidence: 99%
“…First, the literature has found that these policy instruments are associated with a rebound effect (Alberini et al, 2016), whereby potential savings are wiped out by changes in people's behaviour. Second, they encourage free-riding (Houde and Aldy, 2017). Third they need to be financed through, for example, distortionary taxes and finally they are often not cost-effective.…”
Section: Economic and Financial Instrumentsmentioning
confidence: 99%
“…The institutional features of the US appliance market combined with our rich micro-data allow us to study an exhaustive set of energy fiscal policies and highlight issues associated with microfrictions. Our empirical strategy extends our previous work on consumer rebates and energy labels (Houde and Aldy 2017;Houde 2017) and consists of a parsimonious structural demand model that captures heterogeneity in the responses to energy fiscal instruments. We focus on the US refrigerator market over 2008-2012, when local, state, and national policymakers implemented a rich array of fiscal instruments intended to promote energy-efficient purchases.…”
Section: Introductionmentioning
confidence: 99%